Pengaruh Kesadaran Perpajakan dan Pelayanan Fiskus terhadap Kepatuhan Wajib Pajak Orang Pribadi - Nginang, Yusra (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2023)
This research aims to examine the impact of tax awareness and fiscal services on the tax compliance of individual taxpayers in the city of Parepare. The research method used is causal research with a population of individual taxpayers in Parepare, and the sample selection is done through proportional sampling. The data used are subject data from primary data sources, and data collection is conducted using questionnaires. The analysis used is multiple regression analysis. The test results indicate that tax awareness has a significant positive impact on tax compliance, and fiscal services have a significant positive impact on tax compliance. The recommendations from this research are to suggest that the tax officials in the city of Parepare become more proactive in providing information and tax collection to taxpayers, so they understand their tax obligations and avoid sanctions. Furthermore, future research is expected to encompass all tax compliance indicators to better support overall tax compliance.